2020
DOI: 10.24912/jmstkik.v3i2.5656
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Penggunaan Media Sosial Whatsapp Dan Booklet Terhadap Pengetahuan Dan Sikap Siswa Tentang Rokok Di Sma Negeri 13 Medan

Abstract: Smoking is one of the public health problems in Indonesia by remembering that smoking is one of the main risk factors of several chronic diseases that can lead to death. Smoking among adolescents is caused by curiosity or trying out new experiences, trying to eliminate boredom, wanting to be considered more male and want to be accepted in the group. The purpose of this study was to analyze the effect of the use of whatsapp social media and booklets on knowledge about cigarettes and student attitudes at SMA Neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0
7

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 0 publications
2
3
0
7
Order By: Relevance
“…The increase in positive category may be caused the adolescent mothers know the benefits of the booklet. The increase in the average value of attitudes after health education is in line with other research which proves that there was an increase in the average value of attitudes after being given health education using WhatsApp media and booklet [12]. Research by Puspitaningrum also proves that the value of attitude increases by 8% after being given health education [24].…”
Section: The Effect Of Health Education On Changes In Attitudesupporting
confidence: 85%
See 1 more Smart Citation
“…The increase in positive category may be caused the adolescent mothers know the benefits of the booklet. The increase in the average value of attitudes after health education is in line with other research which proves that there was an increase in the average value of attitudes after being given health education using WhatsApp media and booklet [12]. Research by Puspitaningrum also proves that the value of attitude increases by 8% after being given health education [24].…”
Section: The Effect Of Health Education On Changes In Attitudesupporting
confidence: 85%
“…Prevention of stunting in this area can be done by promoting health using Gerakan Melawan Stunting (GENTING) booklet and e-learning by utilizing the video call feature on Whatsapp. Health promotion using booklet media has been proven effective in increasing knowledge and attitudes [12,13]. The lack of knowledge, attitude, and behavior of adolescent mothers caused researchers to be interested in researching the knowledge, attitude, and behavior after being given health education using the GENTING booklet in the Working Area of Neglasari Public Health Center.…”
Section: Introductionmentioning
confidence: 99%
“…In tune with the research that is done by (Gafi, Hidayat, & Tarigan, 2020) showed that the results of the group given WhatsApp media treatment were 5.95 and after being treated with WhatsApp media became 6.95, which means that student knowledge increased after being treated with WhatsApp media. Increased knowledge after given educational health of anaemia is supported by the theory (Notoatmodjo, 2012), which suggests that the education of health is one of the factors that significantly influence knowledge.…”
Section: Knowledgesupporting
confidence: 52%
“…Dengan demikian media cetak mampu mempengaruhi pengetahuan pengunjung secara signifikan dan bernotasi positif. Hal ini sesuai dengan penelitian dari Gafi et al (2020), bahwa media cetak mampu mempengaruhi pengetahuan seseorang. Media cetak mampu mempengaruhi secara signifikan, hal ini dikarenakan Bahasa, materi dan design yang dipaparkan dibuat seenarik mungkin dan senyaman mungkin untuk dilihat, sehingga pengunjung mampu memahami materi lebih cepat dan pemahaman pengunjung dapat nilai lebih baik penyerapannya.…”
Section: Media Cetakunclassified